It's All Under Control: Threat, Perceived Control, and Political Engagement. Issue 3 (8th June 2021) - Smith, Brianna A.
Abstract : The relationship between political threat, anxiety, and political engagement is the subject of a large but mixed body of evidence. While some researchers find that political threat and/or anxiety increase engagement with politics, others find that they lead to disengagement . In this article, I highlight two factors which explain when threat will increase political engagement: perceived control over the threat and individual differences in threat sensitivity. Using an experiment conducted during the 2016 US general election, I show that threats framed in high‐control, preventable terms increase both political interest and reported turnout relative to low‐control, inevitable framing—but only among those who are high in threat sensitivity. These changes in engagement are highly durable, lasting several weeks after participants were first exposed to the threat. I discuss the implications of these findings for political science and more broadly for elections and election outcomes in a political atmosphere that is often saturated with threatening rhetoric.